2003
DOI: 10.3732/ajb.90.6.924
|View full text |Cite
|
Sign up to set email alerts
|

Annulus–pore relationship in Gramineae (Poaceae) pollen: the pore margin ofPariana

Abstract: Pariana, a primitive bamboo, is the only genus in the Gramineae (Poaceae) to have pollen grains without an annulus as part of its single aperture (porate) system. In contrast, the markedly thickened exine layer underlying the pore margin is similar to counterparts in all grass genera. Components of the future annulus in Gramineae pollen develop toward the cytoplasm (proximally) and begin to be pressed outward by an increase in the cytoplasm during the microspore vacuolate stage, culminating in an annulus by ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…Studies of Poaceae pollen grains have revealed a strong correlation between size of pollen grain, pore, and annulus (Skvarla et al, 2003; Joly et al, 2007; Schüler and Behling, 2011a,b; Jan et al, 2014). The results of our own study also showed a relationship between size of pollen, pore, and annulus, as determined through correlation analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of Poaceae pollen grains have revealed a strong correlation between size of pollen grain, pore, and annulus (Skvarla et al, 2003; Joly et al, 2007; Schüler and Behling, 2011a,b; Jan et al, 2014). The results of our own study also showed a relationship between size of pollen, pore, and annulus, as determined through correlation analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these species also inhabit southern Brazil. Some studies (Table 1) have explored the surface of the Poaceae pollen grains through SEM, which has contributed to separation of taxonomic groups (Köhler and Lange, 1979; Linder and Ferguson, 1985; Chaturvedi et al, 1994, 1998; Chaturvedi and Datta, 2001; Skvarla et al, 2003; Datta and Chaturvedi, 2004; Liu et al, 2004, 2005; Perveen, 2006; Kashikar and Kalkar, 2010; Ahmad et al, 2011; Dórea, 2011; Perveen and Qaiser, 2012; Mander et al, 2013, 2014; Nazir et al, 2013; Morgado et al, 2015; Needham et al, 2015; Mander and Punyasena, 2016). However, other studies using light microscopy (LM) have shown morphometric differences in the size of the Poaceae pollen grain species (Salgado-Labouriau and Rinaldi, 1990; Katsiotis and Forsberg, 1995; Joly et al, 2007; Schüler and Behling, 2011a,b; Jan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In Restionaceae and Centrolepidaceae, for instance, Linder and Fergunson (1985) reported many types of annulus apertures, but not the intine thickenings commonly seen in Poaceae, which would indicate independent evolutionary paths. The absence of the annulus in the pollen grain of Poaceae was reported in species of herbaceous bamboos belonging to the genus Pariana (Bambusoideae-Olyreae) (Salgado-Labouriau and Rinaldi, 1990;Salgado-Labouriau et al, 1993;Chissoe et al, 1994;Skvarla et al, 2003). The character 'absence of annulus' or its discrete development, associated with other characters, may be useful in the phylogeny of Poaceae (Skvarla et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Ahmad et al (2011) described the pollen grain morphology of five Poaceae species belonging to three genera of the tribe Chlorideae, stating that grain characters are important in delimiting the Poaceae family at species, genus and tribe levels. The pore diameter as well as the annulus shape and size are the principle characteristics and can be used for distinction between Poaceae species (Beug 1961;Skvarla et al 2003). The author suggested an intraspecific wide range of grain sizes, but did not report the exact annulus size of Poaceae species.…”
mentioning
confidence: 97%